2019
DOI: 10.5539/ijel.v9n6p135
|View full text |Cite
|
Sign up to set email alerts
|

Code-Switching Between Arabic and English: Reasons, Types and Attitudes as Expressed by EFL Female Students at Imam Muhammad Ibn Saud Islamic University

Abstract: This is a preliminary qualitative quantitative survey of the code-switching reasons, forms and attitudes as expressed by Imam Muhammad ibn Saud Islamic University language and translation female students. To achieve this purpose, seventy (70) students responded to an open questionnaire on the various reasons, forms of code-switching and attitudes towards code-switching during the summer semester, 2018. The results revealed that eminent among the reasons behind code-switching was the desire to speak two languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Expressing positive attitudes toward CS was also reported in a number of studies (e.g., Al-Qahtani, 2014;Al Matarneh, 2011;Alhamami, 2019;Alkhawaldeh, 2019;Asmari, 2014;Hleihil, 2001;Omar & Ilyas, 2018;Shuchi & Islam, 2016).…”
Section: Statistical Tests For Positive Attitudesmentioning
confidence: 64%
See 2 more Smart Citations
“…Expressing positive attitudes toward CS was also reported in a number of studies (e.g., Al-Qahtani, 2014;Al Matarneh, 2011;Alhamami, 2019;Alkhawaldeh, 2019;Asmari, 2014;Hleihil, 2001;Omar & Ilyas, 2018;Shuchi & Islam, 2016).…”
Section: Statistical Tests For Positive Attitudesmentioning
confidence: 64%
“…This means that most participants rejected negative attitudes toward CS because it annoyed them when they did not understand the switched language. As for the results for positive attitudes, a number of studies reported that their subjects rejected negative attitudes (Al-Qahtani, 2014;Al Matarneh, 2011;Alhamami, 2019;Alkhawaldeh, 2019;Asmari, 2014;Hleihil, 2001;Omar & Ilyas, 2018;Shuchi & Islam, 2016).…”
Section: Statistical Tests For Negative Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…He said that this happened because of youth's exposure to social media, education, or modernization. Alkhawaldeh (2019) pointed out people's attitudes toward code-switching. He said that some people's views were positive toward code-switching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bilingual or multilingual people can use code-mixing (CM) and code-switching (CS) more often. Many scholars explore the phenomenon of CM and CS in many contexts and situations, such as educational context (Alkhawaldeh, 2019;Alkhresheh, 2015;Hayek, 2016;Kustati, 2014;Susylowati, Sumarlam, Abdullah, & Marmanto, 2019;Zetri, Arasuli, & Aziz, 2018), Islamic religious discourse (Bassiouney, 2013;Ismail, 2015;Stille, 2018;Susanto, 2006;Syam & Fitrawati, 2020;Triana & Eka Saputra, 2018), Christian discourse (Dladla, 2017), media (Octaviana, 2019;Silaban & Marpaung, 2020;Sutrisno & Ariesta, 2019), and leaders' discourse (Purba, 2017;Sugiantari, 2018;Wibowo et al, 2017).…”
Section: Background Of Studymentioning
confidence: 99%